PERKEMBANGAN MATEMATIKA DALAM FILSAFAT DAN ALIRAN FORMALISME YANG TERKANDUNG DALAM FILSAFAT MATEMATIKA - Robin Tarigan (Sepren, 2021)
Philosophy of mathematics does not add a number of new mathematical theorems or theories, so a philosophy of mathematics is not mathematics. The philosophy of mathematics is an area of ​​reflection about mathematics. After studying for a long time, one needs to reflect on learning outcomes by reflecting on the philosophy of mathematics. Mathematics and philosophy are closely related, compared to other sciences. The reason is that philosophy is the base for studying science and mathematics is the mother of all sciences. There are also those who think that philosophy and mathematics are the mother of all existing knowledge. From a historical perspective, the relationship between philosophy and mathematics underwent a very striking development. This article discusses the development of mathematics in philosophy and the flow of formalism contained in the philosophy of mathematics in particular